Peran Dinas Perikanan dalam Pemberdayaan Ekonomi Nelayan untuk Meningkatkan Kesejahteraan Masyarakat Pesisir - Elnada Gefania Syahputri; Fitra Rizal (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The Fisheries Service plays an important role in improving the welfare of fishing communities through various empowerment programs. This study aims to analyze the role of the Fisheries Service of Pacitan Regency in empowering fishermen and its implications for their economic welfare in Sidomulyo Village, Ngadirojo District, Pacitan Regency. This research employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving Fisheries Service officials and members of the fishing community. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that fishermen’s empowerment has been implemented through four governmental roles: regulator, dynamizer, facilitator, and catalyst. These roles are reflected in policy support, business assistance, infrastructure development, and capacity-building programs. The success of these initiatives is supported by the strong work ethic of fishermen and the existence of fishermen’s business groups. However, the program faces challenges, including limited human resource capacity and budget constraints. Furthermore, the empowerment initiatives have contributed to improving fishermen’s welfare, particularly in education (hifz al-nasl), health and living standards (hifz al-nafs), and economic resilience through stable income and effective asset management (hifz al-mal).